2020
DOI: 10.14740/jnr574
|View full text |Cite
|
Sign up to set email alerts
|

May Neutrophil to Lymphocyte Ratio Serve a Role in the Prediction of Clinical Features of Migraine?

Abstract: Background: We aimed to investigate the possible association between the value of neutrophil to lymphocyte ratio (NLR) and some specific features of migraine. Methods:We have included initially all the patients with migraine who applied to our neurology clinic in Yozgat City Hospital during December 2019 and agreed to participate in this study. The demographic and clinical characteristics including migraine subtype (episodic/chronic), headache frequency per month, headache characteristics of all patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In a previous study, it was determined that TTH patients' thrombocyte counts and NLR, PLR, and CRP values were statistically significantly higher [7]. There also are studies relating these ratios to migraine [12,13]. In studies carried out, especially during migraine attacks, it was found that NLR and PLR were higher than in the control group [12].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study, it was determined that TTH patients' thrombocyte counts and NLR, PLR, and CRP values were statistically significantly higher [7]. There also are studies relating these ratios to migraine [12,13]. In studies carried out, especially during migraine attacks, it was found that NLR and PLR were higher than in the control group [12].…”
Section: Discussionmentioning
confidence: 97%
“…There also are studies relating these ratios to migraine [12,13]. In studies carried out, especially during migraine attacks, it was found that NLR and PLR were higher than in the control group [12]. In the literature, there also are studies reporting no significant difference between migraine patients and control groups in terms of NLR and PLR values [14].…”
Section: Discussionmentioning
confidence: 99%